Application of GIS Analyzing Settlement Along Pekan-Kuantan Federal Road - Mohamad Idris, Ali; Youventharan, Duraisamy (Penerbit UMP, 2011)
Improper geotechnical and geological site investigation done before any construction will contribute to serious problems like settlement. Government not only has been spending billions of money to facilitate public with infrastructures but also the same amount of money for maintenance over the years. Therefore researchers around the world are continuously searching for the best method to compute settlements in soil and engineers too are proposing the best practices in improving the ground before the construction. The main aim of this research is to find out if Geographical Information System (GIS) could be used as the one of settlement analysis tool as well as for engineers in verifying their road alignment design. The Pekan-Kuantan Federal Road has been chosen as the study area and available borehole data was utilized using GIS before relevant analysis was conducted. The output of this research was the establishment of settlement database along the study area which assists the researchers in recommending suitable ground treatment and even proposed a virtual alternative route for this road. It is significantly showed that GIS would serve as the most efficient tool in determining road alignment especially in problematic ground such as peat.